PENGARUHÂ PERMAINANÂ TRADISIONALÂ GOBAKÂ SODORÂ TERHADAPÂ PERKEMBANGANÂ MOTORIKÂ KASARÂ DANÂ Â SIKAPÂ KOOPERATIFÂ ANAKÂ TKÂ KELOMPOKÂ BÂ DIÂ KECAMATANÂ SIDOARJOÂ - lita erdiana (Universitas Muhammadiyah Surabaya, 2016)
ABSTRACT ThisÂ studyÂ aimsÂ toÂ determineÂ theÂ influenceÂ ofÂ theÂ traditionalÂ gameÂ gobakÂ sodor againstÂ grossÂ motorÂ developmentÂ andÂ cooperativeÂ attitudeÂ kindergartenÂ childrenÂ inÂ group BÂ inÂ theÂ districtÂ ofÂ Sidoarjo. ThisÂ studyÂ isÂ basedÂ onÂ dataÂ inÂ theÂ fieldÂ indicatingÂ thatÂ aspectsÂ ofÂ grossÂ motorÂ skillsÂ of childrenÂ lessÂ exploitedÂ wellÂ andÂ cooperativeÂ attitudeÂ ofÂ childrenÂ whoÂ doÂ notÂ develop optimally.ThisÂ researchÂ isÂ appliedÂ inÂ theÂ formÂ ofÂ experimentsÂ usingÂ controlÂ groups.Â ThisÂ study usesÂ aÂ designÂ pretestâ€posttestÂ controlÂ groupÂ designÂ withÂ oneÂ kindÂ ofÂ treatment.Â DataÂ were obtainedÂ fromÂ theÂ initialÂ observationÂ andÂ finalÂ observations. Â DataÂ fromÂ observationsÂ obtained asÂ follows:Â TheÂ averageÂ resultsÂ ofÂ initial observationsÂ experimentalÂ groupÂ isÂ 8.95.Â WhileÂ atÂ theÂ endÂ ofÂ theÂ observationÂ afterÂ being treatedÂ traditionalÂ gamesÂ gobakÂ sodorÂ averageÂ yieldÂ grossÂ motorÂ development experimentalÂ groupÂ isÂ 12.75.Â GrossÂ motorÂ developmentÂ inÂ theÂ controlÂ groupÂ the observationÂ ofÂ theÂ initialÂ (pretest)Â anÂ averageÂ ofÂ 8.825.Â WhileÂ atÂ theÂ endÂ ofÂ the observationÂ ofÂ anÂ averageÂ yieldÂ ofÂ 9.6Â grossÂ motorÂ development.Â TheÂ averageÂ resultsÂ of theÂ developmentÂ ofÂ socialÂ behaviorÂ inÂ theÂ experimentalÂ groupÂ theÂ initialÂ observation, namelyÂ 9.05.Â AtÂ theÂ endÂ ofÂ theÂ observationÂ ofÂ anÂ averageÂ ofÂ 12.3.Â WhileÂ theÂ average results ofÂ theÂ developmentÂ ofÂ socialÂ behaviorÂ inÂ theÂ controlÂ group:Â 9Â fromÂ theÂ initial observationÂ andÂ theÂ observationÂ ofÂ theÂ endÂ ofÂ anÂ averageÂ 9.775 ANOVAÂ testÂ resultsÂ obtainedÂ asÂ follows:Â statisticalÂ analysisÂ ofÂ dataÂ grossÂ motor developmentÂ valueÂ ofÂ FÂ =Â 31.778Â isÂ greaterÂ thanÂ FÂ tableÂ =Â 4.00Â andÂ statisticalÂ analysisÂ of socialÂ behaviorÂ developmentÂ dataÂ obtainedÂ valueÂ ofÂ FÂ =Â 19.837Â isÂ greaterÂ thanÂ FÂ tableÂ = 4.00 MutivariatÂ TestÂ resultsÂ obtainedÂ asÂ follows:Â theÂ valueÂ ofÂ PÂ valuesÂ forÂ fourÂ different multivariateÂ testÂ onÂ theÂ traditionalÂ gameÂ gobakÂ sodorÂ overallÂ lessÂ thanÂ 0.05Â isÂ 0.Â With demikiam noÂ significantÂ influenceÂ ofÂ theÂ independentÂ variableÂ onÂ theÂ dependentÂ variable all BasedÂ onÂ theÂ analysis,Â itÂ canÂ beÂ concludedÂ thatÂ theÂ traditionalÂ gameÂ gobakÂ sodor effectÂ onÂ grossÂ motorÂ developmentÂ andÂ socialÂ behaviorÂ ofÂ children. Â KeyWords:Â TraditionalÂ GamesÂ GobakÂ Sodor,Â GrossmotorÂ skills,Â SocialÂ Behavior.